2016
DOI: 10.15537/smj.2016.11.16268
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and major non-communicable diseases among physicians in Central Saudi Arabia

Abstract: Objectives:To evaluate levels of physical activity among physicians in Riyadh, Saudi Arabia and to study the possible factors affecting physical inactivity. In addition, the study aims to estimate the prevalence of major non-communicable diseases (NCDs) and a possible correlation between physical inactivity and major NCDs.Method:A cross-sectional approach was used for this study conducted on 370 randomly-selected outpatient physicians of both genders working at 4 leading healthcare institutions in Riyadh, Kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 18 publications
(24 reference statements)
0
34
1
2
Order By: Relevance
“…Fast food intake and soft drinks consumption were higher among men than women . Another study indicated that most of the nurses who worked shift duty ate more fast food and unhealthy snacks .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Fast food intake and soft drinks consumption were higher among men than women . Another study indicated that most of the nurses who worked shift duty ate more fast food and unhealthy snacks .…”
Section: Resultsmentioning
confidence: 98%
“…First, the results of the 84 eligible correlate studies are described, followed by the data on the seven intervention studies …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8,9] Many studies showed that the Saudi population don't practice physical activity either in a sufficient duration or adequate frequency and this could be attributed to ignorance, not having time, lack of facilities and lack of motivation. [10][11][12][13][14] Also, there is a lack in the studies considering physical inactivity in KSA and its complications. [14] This study aimed tostudy the KAP of Saudi women regarding physical activity in KSA.…”
Section: Introductionmentioning
confidence: 99%